2021
DOI: 10.1002/path.5676
|View full text |Cite
|
Sign up to set email alerts
|

BOP1 confers chemoresistance of triple‐negative breast cancer by promoting CBP‐mediated β‐catenin acetylation

Abstract: Chemoresistance is a major obstacle to the treatment of triple‐negative breast cancer (TNBC), which has a poor prognosis. Increasing evidence has demonstrated the essential role of cancer stem cells (CSCs) in the process of TNBC chemoresistance. However, the underlying mechanism remains unclear. In the present study, we report that block of proliferation 1 (BOP1) serves as a key regulator of chemoresistance in TNBC. BOP1 expression was significantly upregulated in chemoresistant TNBC tissues, and high expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…We found that BOP1 mRNA was upregulated in 25 types of cancer and downregulated in LAML and THCA samples. The results were consistent with previous studies in gastric cancer [ 8 ], colorectal cancer [ 10 , 20 ], prostate cancer [ 9 ], triple-negative breast cancer [ 21 ], and hepatocellular carcinoma [ 13 ]. These findings suggested that BOP1 is likely to operate as an oncogene in most tumors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that BOP1 mRNA was upregulated in 25 types of cancer and downregulated in LAML and THCA samples. The results were consistent with previous studies in gastric cancer [ 8 ], colorectal cancer [ 10 , 20 ], prostate cancer [ 9 ], triple-negative breast cancer [ 21 ], and hepatocellular carcinoma [ 13 ]. These findings suggested that BOP1 is likely to operate as an oncogene in most tumors.…”
Section: Discussionsupporting
confidence: 93%
“…The Kaplan–Meier survival analysis showed that increased BOP1 expression was correlated with poor OS in nine tumors. Similarly, it was previously reported that BOP1 expression is related to shorter survival period in patients with prostate carcinoma [ 9 ], triple-negative breast cancer [ 21 ], gastric cancer [ 8 ], and hepatocellular carcinoma [ 24 ], and BOP1 promotes the development of these cancers. Moreover, BOP1 expression might be used as a potential prognostic marker in patients with tumor metastases [ 9 , 21 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, dependent on HATs as mentioned above, multiple molecules are involved in modulating β-catenin acetylation. For instance, Li et al found that blocking proliferation 1 (BOP1) can initiate β-catenin acetylation that is dependent on CBP to strengthen the drug resistance of breast cancer [ 26 ]. Forkhead box protein P1 (FOXP1) has been proven to activate this signaling by increasing β-catenin acetylation in different biological processes [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CREPT could enhance the association of p300 with β-catenin, thus promoting p300-mediated β-catenin acetylation and stabilization ( 50 ). Li et al reported that block of proliferation 1 (BOP1) could increase Wnt/β-catenin signaling by enhancing CBP recruitment to β-catenin, thus promoting β-catenin acetylation and activation ( 51 ). A recent study showed that Bcl-3 could enhance the Wnt signaling cascade by maintaining the acetylation of β-catenin at K 49 in colorectal cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%